Conceptualizing Pain and Personhood in the Periviable Period: Perspectives from Reproductive Health and Neonatal Intensive Care Unit Clinicians. (January 2021) - Andaya, Elise; Campo-Engelstein, Lisa
Abstract: In 2020, the Pain Capable Unborn Child Protection Act was brought to an unsuccessful Senate vote for the third time in five years. The Act seeks to prohibit abortions after 20 weeks post-conception based on the scientifically contested claim that fetuses are at that point capable of feeling pain. It thus seeks to undermine Roe v. Wade's viability standard by asserting that the capacity for pain perception is sufficient for "compelling governmental interest" in fetal life. The ability of many NICUs to offer life-sustaining interventions for periviable neonates means that, in many states, neonatologists and physicians who provide second-trimester abortion care may manage cases of the same gestational age. Given this overlap, this qualitative study examines how clinicians think about the capacity of periviable entities to feel pain and how these ideas shape clinical practice and understandings of compassionate care. Drawing on twenty semi-structured interviews conducted between June 2019 and April 2020 with clinicians providing second-trimester abortion care and NICU care in the Northeast United States, it examines how pain is "known" in the periviable period and how clinicians think about pain in relationship to personhood. A key finding is that the meaning of pain and implications for clinical care is shaped by the anticipated futures and personhood status of periviable entities as determined by pregnant people and families of neonates. Clinicians also stated that concerns around the alleviation of suffering, defined as long-term or chronic distress for pregnant people and/or neonates and their families, were more pressing than the potential experience of short-term physical pain. Legislative attempts to make contested ideas of "fetal pain" the basis for "governmental interest" ignores other forms of suffering that might result from denial of options, and potentially places clinicians at odds with their own conceptions of competent and compassionate care. Highlights: The recognition of pain is both subjective and objective. Clinicians view limiting suffering as more important than eliminating pain. There are disciplinary differences in beliefs about timing of pain perception. Clinicians view the capacity for pain as insufficient to determine personhood. Periviable pain is meaningful primarily in relation to anticipated futures.